2016
DOI: 10.1002/lt.24342
|View full text |Cite
|
Sign up to set email alerts
|

Outflow reconstruction for right liver allograft with multiple hepatic veins: “V‐plasty” of hepatic veins to form a common outflow channel versus 2 or more hepatic vein–to–inferior vena cava anastomoses in limited retrohepatic space

Abstract: Outflow reconstruction in living donor liver transplantation (LDLT) is certainly difficult in limited retrohepatic space with using right liver grafts with venous anomalies. Venoplasty of the inferior right hepatic veins (IRHVs) and middle hepatic vein (MHV) reconstruction using synthetic grafts to form a common outflow channel or a second venocaval anastomosis are available options. We aim to compare outcomes of LDLT recipients who underwent outflow reconstruction with a "V-Plasty" technique and outcomes of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The ePTFE synthetic grafts are commonly used interpositional conduits during the backtable venoplasty procedure of such liver allografts, with excellent short- and long-term graft outcomes [2,3,8]. Thrombosis of the graft and possible risk of infections, although rare, are the possible complications of ePTFE use in LDLT recipients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The ePTFE synthetic grafts are commonly used interpositional conduits during the backtable venoplasty procedure of such liver allografts, with excellent short- and long-term graft outcomes [2,3,8]. Thrombosis of the graft and possible risk of infections, although rare, are the possible complications of ePTFE use in LDLT recipients.…”
Section: Discussionmentioning
confidence: 99%
“…ePTFE graft migration into the surrounding hollow viscous organs causing perforation has been described recently, and tends to narrow the safety margin for the use of the ePTFE synthetic grafts [57]. However, such complications are fortunately rare and the safety and feasibility of ePTFE use in LDLT has been proven by several studies [2,3,8,10]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We do not have cryopreserved vascular grafts at our centre, and due to the underlying surgical complexity of harvesting donor or recipient autologous veins during LDLT, we prefer ePTFE vascular conduits for venous reconstruction. In our earlier studies, we have reported the safety and feasibility of ePTFE synthetic grafts for venous reconstruction for vessels such as inferior vena cava and middle hepatic venous tributaries of the right liver allograft without any thrombotic complications (10)(11)(12). By far, the role of the ePTFE graft for portal vein reconstruction remains scarce (3).…”
Section: Discussion Discussionmentioning
confidence: 99%